Contrasts among cationic phytochemical landscapes in the southern United States. Issue 5 (4th October 2022) - Santiago‐Rosario, Luis Y.; Harms, Kyle E.; Craven, Dylan
Abstract: Understanding the phytochemical landscapes of essential and nonessential chemical elements to plants provides an opportunity to better link biogeochemical cycles to trophic ecology. We investigated the formation and regulation of the cationic phytochemical landscapes of four key elements for biota: Ca, Mg, K, and Na. We collected aboveground tissues of plants in Atriplex, Helianthus, and Opuntia and adjacent soils from 51, 131, and 83 sites, respectively, across the southern United States. We determined the spatial variability of these cations in plants and soils. Also, we quantified the homeostasis coefficient for each cation and genus combination, by using mixed‐effect models, with spatially correlated random effects. Additionally, using random forest models, we modeled the influence of bioclimatic, soil, and spatial variables on plant cationic concentrations. Sodium variability and spatial autocorrelation were considerably greater than for Ca, Mg, or K. Calcium, Mg, and K exhibited strongly homeostatic patterns, in striking contrast to non‐homeostatic Na. Even so, climatic and soil variables explained a large proportion of plants' cationic concentrations. Essential elements (Ca, Mg, and K) appeared to be homeostatically regulated, which contrasted sharply with Na, a nonessential element for most plants. In addition, we provide evidence for the No‐Escape‐from‐Sodium hypothesis in real‐world ecosystems, indicating that plant Na concentrations tend to increase as substrate Na levels increase. Abstract : Plants are key conduits that link substrate to higher trophic levels in food webs and biogeochemistry cycles. In this study, we set out to characterize how the phytochemical landscape of cations is formed and maintained across the southern United States and show some insights into how essential (Ca, Mg and K) and nonessential (Na) elements for plants, are distributed across in tissues across a heterogeneous landscape. We also show how plants homeostatically regulate essential elements regardless of high substrate variation, a pattern contrary to that of nonessential elements like Na. We also show field evidence for the No‐Escape‐from‐Sodium hypothesis indicating that plant Na concentrations tend to increase as substrate Na levels increase.